2002
DOI: 10.1136/bmj.325.7372.1070
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrest and ventricular arrhythmia in patients taking antipsychotic drugs: cohort study using administrative data

Abstract: Objective To examine the rates of cardiac arrest and ventricular arrhythmia in patients with treated schizophrenia and in non-schizophrenic controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
7
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(178 citation statements)
references
References 15 publications
7
156
7
6
Order By: Relevance
“…Case-control studies and epidemiological data show increased incidence of sudden cardiac death in psychiatric patients taking antipsychotics (Hennessy et al 2002). Other studies have revealed the potential of several phenothiazines to induce acquired L-QT syndrome, with prolonged QT c intervals and a high risk for both TdP and sudden cardiac death (Reilly et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies and epidemiological data show increased incidence of sudden cardiac death in psychiatric patients taking antipsychotics (Hennessy et al 2002). Other studies have revealed the potential of several phenothiazines to induce acquired L-QT syndrome, with prolonged QT c intervals and a high risk for both TdP and sudden cardiac death (Reilly et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical aspects of acute treatment with haloperidol and its impact on cardiovascular system, primarily QT interval prolongation and associated arrhythmias, were studied repeatedly (Metzger and Friedman 1993;Hennessy et al 2002;Beach et al 2013). Effects of the acute and/or chronic exposure to haloperidol have been also studied on various biomodels and species, including rat (Fialova et al 2009), guinea pig (Testai et al 2007;Fialova et al 2009), and rabbit (Dhein et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Most antipsychotics and some antidepressants may be associated with QTc prolongation (Glassman, 2005). Patients using AP have higher rates of cardiac arrest or ventricular arrhythmias than controls, with ratios ranging from 1.7 to 5.3 (Ray et al, 2001;Hennessy et al, 2002;Reilly et al, 2002). Antipsychotics associated with a greater risk of QTc prolongation include pimozide, thioridazine and mesoridazine among the FGAs (Vieweg, 2002;Reilly et al, 2002) and sertindole and ziprasidone among the SGAs (Thomas et al, 2010).…”
Section: Drugmentioning
confidence: 99%